Flavonoid Glycosides from Lagonychium farcatum and Herminiera elaphroxylon - H. El-Sayed, Nabil; El-Sherbeiny, A.E.A.; Ashraf, M.S.; J. Mabry, Tom (Asian Journal of Chemistry, 2010)
From the methanolic water extract of Lagonychium farcatum (Banks + sol.) Bubr, recently, known as Prosopis faracata (Banks + sol.) Macbride and Herminiera elaphroxylon (Guill + perr.) (Fabiaceae) 13 known flavonoids (C-glycosides, monoglucosides, di and triglycosides and aglycones) were isolated and identified.